Ability of Exogenous or Wort Endogenous Enzymes to Release Free Thiols from Hop Cysteinylated and Glutathionylated S-Conjugates. (2nd January 2023) - Chenot, Cécile; Willemart, Guillaume; Gros, Jacques; Collin, Sonia
Abstract: Following identification of the substantial pool of aromas represented by cysteinylated and glutathionylated precursors in hop, many studies have focused on developing methods for releasing volatile thiols based on chemical hydrolysis or yeast activity. The present work aimed to evaluate the release activity of either commercially available exogenous enzymes or endogenous wort enzymes (issued from hop or malt) on synthetic Cys- or G-precursors of 3SHol, 3SPol, 3SHptol, 3S4MPol and 4S4M2Pone. In a model medium at pH 7.7, both apotryptophanase and cystathionine β-lyase appeared very efficient on Cys-adducts (up to 77.9% release). Interestingly, a slight proportion of this release (up to 0.9%) appeared to result from chemical hydrolysis. In polyphenols rich media such as hop and beer, total release was much lower (under 0.2%). For release from G-adducts, a combination of γGT and apotryptophanase proved to be effective, highlighting for the first time the ability of β-lyase activity to release free PFTs also from CysGly-adducts. The best release rates (above 2% for all thiols) were obtained with a two-step incubation: 75 units γGT with synthetic glutathionylated precursors for 16 h at 37 °C in the presence of alanine followed by apotryptophanase for 7 h at room temperature. The alternative combination of γGT with S. cerevisiae was found to release free thiols more efficiently than yeast activity alone. Compared to commercially available enzymes, endogenous enzymes extracted from hop or malt displayed lower efficiency (below 0.3% for γGT activity and below 0.002% for β-lyase).